Digitizing Arudh and Qowafi Classics as Android-Based Student Learning Media Using Flutter - Syafiih, M (Malikussaleh University, Aceh, Indonesia, 2022)
The book Arudh Qawafi is the work of the Caretaker of the At-Tarbiyah Guluk-Guluk Sumenep Islamic Boarding School, namely K.H. Wakid Yusuf, S.E. The book discusses Arabic literature in the form of Syi'ir and Nadham. The 2nd son of K.H. Nurul Huda Basyir has several religious texts, one of which is the book Arudh Qawafi which is regularly reviewed by students majoring in Language (Arabic Literature). The religious texts or the works of the caregivers are still in the form of printed media, namely books, therefore in this digitalization era, the role of the santri to develop the field of information technology is very necessary. This study aims to build an Android-based application in order to make it easier for students, alumni, and sympathizers to access the Arudh Qawafi Book practically. This application development applies the Extreme Programming (XP) software development methodology. Extreme Programming has several advantages, namely that it can perform updates without impacting the overall system design. This method is one of the methodologies that supports the acceleration of the development of a system with a minimum number of teams and produces software that meets the needs, including the planning phase, design phase, coding phase, and testing phase. By using the open source Flutter Framework, the Arudh Qawafi book application can be accessed via mobile more effectively and efficiently.